Analisis Sosialisasi Dan Pemahaman Perpajakan Terhadap Efektivitas Insentif Pajak Pada Masa Pandemi Covid-19 - Setyo Mahanani; Sri Retnoningsih; Muhammad Naufal Syarif (Politeknik Ganesha Medan, 2022)
This study analyzes how the tax incentive policies that have been given to MSME actors. This research was conducted in one of the capital areas of Semarang regency, namely Ungaran. The problem in this observation is to examine how a policy in the form of tax incentives provided by the government during the COVID-19 pandemic can be accepted or enjoyed by taxpayers, especially MSME actors. This observation aims to determine how the socialization of taxation and understanding of taxation on the issuance of Government Regulation no. 44 of 2020 has an influence on the effectiveness of providing tax incentives to taxpayers. This research is a quantitative descriptive study with the data analysis tool used is SPSS version 22. This study uses primary data. Information collection techniques or data collection in this study used questions or questionnaires. The results showed that tax socialization can have a positive effect on the effectiveness of tax incentives and understanding of taxation can also have a positive effect on the effectiveness of tax incentives. With good taxation socialization and a good understanding of taxation, the effectiveness of providing tax incentives for taxpayers whose taxes are provided by the government during the COVID-19 pandemic will increase.